Substrate Temperature Effect on Charge Transport Performance of ZnO Electron Transport Layer Prepared by a Facile Ultrasonic Spray Pyrolysis in Polymer Solar Cells - Jiang Cheng; Rong Hu; Qi Wang; Chengxi Zhang; Zhou Xie; Zhangwen Long; Xin Yang; Lu Li (International Journal of Photoenergy)
A novel ultrasonic spray pyrolysis for high-quality ZnO films based on zinc-ammonia solution was achieved in air. To investigate the structural and optical properties as well as the performance of polymer solar cells (PSCs), ZnO films at different substrate temperatures and thicknesses were prepared. The performance of poly(3-hexylthiophene):[6,6]-phenyl C61-butyric acid methyl ester (P3HT:PCBM) based PSC was found to be improved due to the ZnO films. The crystal structure and roughness of the ZnO films fabricated at different temperatures were found to affect the performance of PSCs. The optimized power conversion efficiency was found to be maximum for PSCs with ZnO films prepared at 200°C. The growth process of these ZnO films is very simple, cost-effective, and compatible for larger-scale PSC preparation. The precursor used for spray pyrolysis is environmentally friendly and helps to achieve ZnO film preparation at a relative low temperature.